Effects Of Aging, Temperature, Moist Aggregates And Filler Type On Performance Of Warm Mix Asphalt Incorporating Rh-Wma Additive - Aburawi, Bashir M. Bashir (2017)
Conventional Hot Mix Asphalt (HMA) has been the primary material used in pavement in past decades. Recently, compared to conventional HMA, Warm Mix Asphalt (WMA) has shown great potential and offers benefits not given by HMA, since the WMA can be produced at lower temperatures without affecting pavement performance. Since WMA additives can reduce the binder viscosity, the production and compaction temperatures can be lowered, compared to conventional HMA. One of the additives used to produce WMA is a type of wax named RH-WMA. In this thesis, the rheological properties of a conventional a virgin PG64 asphalt binder with and without RH-WMA at different aging conditions were investigated. The overall rheological binder tests results indicated that RH-WMA content had significant effects on the rheological parameters of asphalt binders in terms of viscosity, G*/sin δ and G*sin δ. Image analysis technique was used to classify the adhesive failure by using impact test. The impact test was conducted on a newly fabricated mould and the effects of aging conditions and test temperatures of asphalt binder incorporating RH-WMA were investigated. The analysis results showed that short-term aging and long-term aging of asphalt binder increased the percentage of adhesion failure. The construction temperature (mixing and compaction) was reduced by the addition of RH-WMA additive due to viscosity reduction. However, the reduction of mixing temperatures may prevent moisture from being completely evaporated from the aggregate and thus, effect the asphalt binder bond, making the mixture more susceptible to stripping. Two anti-stripping additives, namely hydrated lime and Pavement Modifier (PMD) were used to reduce the destructive effects of moisture. Effects of RH-WMA content, production and testing temperatures on mixture performance were investigated in terms of indirect tensile strength, resilient modulus and creep stiffness. The result indicates that both ITS and MR decreased as the RH-WMA content increased at the respective test and mixing temperatures. The effects of incomplete drying of aggregates on the mechanical properties of asphalt mixtures were clearly evident in this thesis. Therefore, the use of fully dried aggregates was important in ensuring satisfactory mix performance. Mixes prepared with 3% RH-WMA and compacted at 125°C° exhibit the best performance compare with HMA. Specimen incorporating PMD filler improved resistance to stripping compared to mixes with hydrated lime filler regardless of compaction temperature. The test results also indicated that aging improved the moisture resistance of WMA.